1980
DOI: 10.1203/00006450-198008000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Levels of Energy Substrates and Evidence for Renal Glucose Production in the Baboon Infant

Abstract: SummaryThe age-related changes in fasting arterial levels of energy substrates and insulin were studied at birth and/or 6 wk in eleven baboon infants. In addition, the renal contribution to glucose release in the primate infant was estimated. Arterial blood glucose levels were similar in six fasted newborns and in nine fasted 6-wkold infants. Arterial blood lactate, alanine, pyruvate, glutamate, and glutamine levels were significantly higher ( P < 0.01) in the new born animals, and /3-hydroxybutyrate was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These relatively low splanchnic glucose production rates compared to new glucose production rates determined in some human neonates in the postabsorptive state may reflect adaptation to fasting. Fur-ther, we have reported that the mean renal contribution to glucose production in the baboon neonate is 1.8 mg/min.Kg compared to 0.6 mg/min kg in the older infant baboon (20). This suggests that glucose production by liver and kidney in the neonate is approximately 4.4 mg/min kg and in the older infant is approximately 3.4 mg/min.kg.…”
Section: Alanine Uptake F ~M O L E S / M L N )mentioning
confidence: 75%
See 2 more Smart Citations
“…These relatively low splanchnic glucose production rates compared to new glucose production rates determined in some human neonates in the postabsorptive state may reflect adaptation to fasting. Fur-ther, we have reported that the mean renal contribution to glucose production in the baboon neonate is 1.8 mg/min.Kg compared to 0.6 mg/min kg in the older infant baboon (20). This suggests that glucose production by liver and kidney in the neonate is approximately 4.4 mg/min kg and in the older infant is approximately 3.4 mg/min.kg.…”
Section: Alanine Uptake F ~M O L E S / M L N )mentioning
confidence: 75%
“…Certainly, similar to reports in adult man (7), we have identified a relationship between arterial plasma lactate levels and splanchnic lactate uptake, as well as a relationship between arterial lactate and glucose release. In previous studies of renal glucose production using the same methodology, glucose production could also be related to arterial lactate (20). It may be noted that, although in adult man lactate normally accounts for less than 50% of total gluconeogenic equivalents taken up by the splanchnic bed (9), studies of the neonates of several species (29) would tend to substantiate the primacy of lactate as a gluconeogenic precursor in early life.…”
Section: Alanine Uptake F ~M O L E S / M L N )mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies of total glucose turnover have not been able to demonstrate significant gluconeogenesis from either lactate or alanine (22); since the net glucose production by the kidney is a small percentage of total glucose turnover, it may not be possible to detect it. Renal gluconeogenesis has been reported to occur in the neonatal baboon and adult sheep (23,24); in preliminary studies we have demonstrated renal gluconeogenesis from I4C-lactate in fetal lambs late in gestation (Gleason CA, Iwamoto HS, Rudolph AM, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%